Responses of grain yield and nutrient accumulation to water and foliar fertilizer management in upland and wetland rice varieties - Natdanai Juntakad (2018)
© 2018 Natdanai Juntakad, Sittichai Lordkaew, Sansanee Jamjod and Chanakan Prom-u-thai. This study evaluated the effects of water and fertilizer managements on grain yield and nutrient accumulation in upland and wetland rice varieties. The two rice varieties representing upland (KH CMU) and wetland (CNT1) ecotypes were grown in different water conditions and fertilizer managements. The interaction between variety and water condition had significantly affected on grain yield and straw dry weight. The water condition and fertilizer management were also affected on grain nutrient concentrations differently between the two varieties. The difference in responses to grain nutrients between the two rice varieties representing their original ecotypes of wetland and lowland is the key factor with respect to the proper management of water and fertilizers in order to maximize in both grain yield and nutrition. This knowledge is useful for the proper management of water and fertilizers for improving grain yield and nutrient accumulation. However, increasing the number of rice varieties in each upland and wetland ecotypes is needed to confirm the responses to water and fertilizer management in the future study.